PENERAPAN ASAS KEADILAN DALAM PROSES PENYELESAIAN HAK ATAS TANAH UNTUK KEGIATAN PERTAMBANGAN - Nakamnanu, Manuel Defender (Justitia et Pax, 2025)
Mining activities are one of the fields that provide a large contribution to state revenue through investment in the mining sector. To increase investment in mining, the government has changed several times the legal policies relating to the implementation of mining activities in Indonesia. Starting from centralized laws through Law Number 11 of 1967 concerning Basic Mining Provisions, which was later revoked by Law Number 4 of 2009 which gave more roles to local governments related to the granting of mining licenses, and further amended by Law Number 3 of 2020 which again adhered to a centralized system in granting mining licenses. Talking about mining activities, things that need to be seen are also related to the settlement of land rights for mining interests. In the three rules above, it implicitly regulates the settlement of land rights for mining interests, but none of the three rules guarantee and provide legal protection and a sense of justice for land rights voters. This is illustrated by the weak position of land rights holders in the process of resolving land rights. In this paper the author takes the formulation of the problem, namely whether the principle of justice has been applied in the process of resolving land rights between land rights holders and IUP holders. Also the method used in this research is based on library research. The results of this study indicate that the principle of justice has not been applied in the process of implementing land rights settlements.